Logistics Distribution Perspective in the Fisheries Sector to Support West Sulawesi's Readiness as a Supporting Region for the New Capital City - Fauzan, Muhammad; Ariyandani, Nur (Economics and Business Journal (ECBIS), 2024)
The study aims to explore the logistics distribution perspective in the fisheries sector of West Sulawesi. It focuses on supporting the region's readiness as a supporting area for the new National Capital (IKN) by examining government policies, infrastructure readiness, and supply chain management in the fisheries sector. The research employs a qualitative approach using a literature review combined with observation and interviews with key stakeholders in the fisheries sector. The study includes a feasibility analysis and utilizes a SOAR (Strengths, Opportunities, Aspirations, Results) analysis to develop strategic recommendations for logistics and infrastructure improvements. The findings reveal that West Sulawesi has significant potential to support IKN through its fisheries sector, given its strategic location and existing infrastructure. However, challenges such as limited cold storage facilities, infrastructure readiness, and supply chain coordination need addressing. The government’s draft Presidential Regulation (RPerpres) outlines a plan for port development and cold storage expansion to improve logistics. The study also suggests that collaboration with the private sector and technological adoption could enhance distribution efficiency and product quality. The research contributes to logistics and supply chain literature by addressing the specific challenges and opportunities in the fisheries sector of a developing region like West Sulawesi. It provides an original perspective on how regional policies and infrastructure development can support national capital projects and meet food supply demands while promoting sustainable practices in the fisheries industry